PENGARUH STORE ATMOSPHERE, KEBERAGAMAN PRODUK DAN KUALITAS PELAYANAN TERHADAP MINAT BELI ULANG COFFEE SHOP MANAKALA BINTARO - Adinda Surya Luthfiyanti (JURNAL ILMIAH EDUNOMIKA, 2026)
In keeping customers to keep buying and coming, Store Atmosphere is a very important characteristic for every business. It plays a role in creating a comfortable atmosphere for consumers and makes them want to linger in the store. This study aims to prove that there is a relationship between the influence of Store Atmosphere, product diversity and service quality on repurchase intention. There were 68 respondents selected as samples. The data testing technique used was Multiple Linear Regression analysis performed using statistical calculations via SPSS v 26.0. The results of the study show that repurchase intention is significantly influenced by store atmosphere, product diversity, and service quality both partially and simultaneously. A comfortable store atmosphere yields a positive impact on consumer repurchase decisions. Therefore, coffee shop management must prioritize attractive atmosphere configurations, product availability, and reliable service interactions. Keywords: store atmosphere, product diversity, service quality, repurchase intention